Ni–Co coordination hollow spheres for high performance flexible all-solid-state supercapacitor. (20th March 2020) - Chen, Lingxue; Ou, Dawei; Zhang, Guochi; Yan, Jian; Liu, Jiaqin; Wang, Zhaoming; Wang, Yan; Cui, Jiewu; Zhang, Qi; Zhang, Yong; Hu, Xiaoye; Wu, Yucheng
Abstract: In this work, hollow spherical nickel-cobalt coordination polymer (Ni–Co/CP) have been synthesized. The hollow structure would facilitate the transport of ions, meanwhile the lamellar sheets may provide more active sites, which are of benefit to achieve high electrochemical performance. The Ni–Co/CP exhibits a high specific capacity of 758.8C g −1 at 0.5 A g −1 . At 20 A g −1, the specific capacity is still as high as 584 C g −1 . The capacity remains 84.6% of its initial value after 5000 cycles. Furthermore, all-solid-state supercapacitors have been assembled using Ni–Co/CP, polybenzimidazole (PBI) doped with KOH and activated carbons (AC) (Ni–Co/CP//PBI-KOH//AC). A high cell specific capacitance of 166.9 F g −1 have been achieved at 1 A g −1 with applied potential difference up to 1.8 V, which corresponds to a specific energy of 75.1 W h kg −1 at 900 W kg −1 ; the capacitance retention remains 85.5% after 8000 cycles suggesting the good stability. Moreover, the device with a large size (2*7 cm) exhibits good flexibility under bending and folding conditions. It also exhibits a cell specific capacitance of 169.5 F g- 1 at 0.5 A g −1 . These results indicate that the Ni–Co/CP and PBI based flexible all-solid-state supercapacitors are very competitive in the future applications of flexible and wearable electronics. Graphical abstract: Figure caption(a) The specific capacity of the Ni–Co/CP at different current densities and the inset is FESEM images of the Ni–Co coordination hollow spheres. (b) The Ragone plots of the Ni–Co/CP//PBI-KOH//AC all-solid-state supercapacitor. (c) Electrochemical performance of the ASC flexible supercapacitance (1 × 6 cm): specific performance of the device at different current densities and the inset is the pictures of flexible device at different bending radius. Image 1 Highlights: Hollow sphere-like NiCo coordination composed of nanosheets have been prepared. A high specific capacity of 758.8C g −1 at 0.5 A g −1  has been achieved. All-solid-state devices assembled using PBI electrolyte are foldable. The all-solid-state devices deliver a high specific energy of 75.1 Wh kg −1 .